Digital social support for undergraduate students during COVID-19: Pivotal support for the digital transformation - Shaista Rashid; Orchida Fayez; Hala Ismail; Raheen Fatimah Khan (SAGE Publishing, 2021)
Background: In a time of crisis, such as the COVID-19 pandemic, digital social support can prove helpful in buffering the stress and anxiety especially for students whose lives were being affected both socially and academically. The present study aims to explore the emotional and informational social support available to students during the online transformation of their education. It further investigates factors affecting anxiety and stress among students. Design and Methods: An online survey was administered among 479 undergraduate students at a private university in Saudi Arabia from 2nd March till 17th June 2020. Descriptive analysis was used to report the findings of students' self-reported data. Results: The results revealed that more than 70% of the students reported that they were satisfied with the informational and emotional support available to them via digital platforms. However, they felt less connected with the teachers and academic administration. Feeling sick (46%), being locked down at homes and isolation (43%) were major causes of stress and anxiety. 71% of the students reported their ability to keep themselves busy, however, only 55% of students mentioned that they did not feel lonely while confined to their homes. In these circumstances, the continuation of studies via online platforms helped students reduce stress and anxiety (52%). Conclusions: Although this online transformation was not planned, the university was able to provide adequate informational support to the students. However, students were dependent upon friends, family and relatives for emotional support. The results of the study point towards the need of training for teachers and academic administrative staff in order to better address students' needs for social support during the crisis.  The results also contribute to the body of data reporting the various effects of the COVID-19 pandemic on students in a way to reach a sustainable framework for supporting students.